Encoded Territory : The Blockchain-based Metaverse as a Special Environment of International Law - Ahonen, Elias (My University, 2022)
Built on private-key encryption, the blockchain metaverse presents challenges to the international order due to the limited ability of states generally to intervene in metaverse-based actions. This article-based dissertation explores questions regarding the practical limits of state power within the metaverse using a case study approach combining actual and theoretical metaverse-based actions with implications of various legal strategies employable by states to ‘tame’ the metaverse. The research is expected to demonstrate that the ability for states to claim jurisdiction, audit and enforce taxation, compel action, protect rights of people, and investigate crime is reduced in a way comparable to legal environments like that of an unfriendly foreign country, or those dealt with in the fields of maritime law and space law, leading to the conclusion that the metaverse influences the balance of global power and constitutes a sui generis environment from the perspective of international law.
Keywords: blockchain, metaverse, cryptocurrency, DAO, NFT, decentralized autonomous organization, non-fungible token, bitcoin, ethereum, ERC-20, minting, mint pass, loot box, gambling, axie infinity, bored ape yacht club, BTC, ETH, APE, RON, AXS, SLP, international law, sui generis, taxation, tax, private key, encryption, sovereignty, law enforcement, IP rights, YGG, Yield Guild Games, regulation